Analysis of brushless DC motor in prototype hydrogen Fuel Cell Electric Vehicle (FCEV) for high efficiency performance at different driving technique / Norhisyam Makmur Ismail - Ismail, Norhisyam Makmur (2015)
One of the requirements for the prototype hydrogen fuel cell electric vehicle competing in 2015 Shell Eco Marathon Asia is that it must travel furthest using least amount of energy. This paper reports the simulation and experimental analysis performed on brushless dc motor used in the vehicle for high efficiency performance at different driving techniques. Results obtained from the test show that by operating at certain speed, high efficiency performance of the motor can be achieved. Hence, its enable the vehicle is able to travel furthest using least amount of energy.